2013
DOI: 10.1007/s00198-013-2415-5
|View full text |Cite
|
Sign up to set email alerts
|

What determines health-related quality of life in hip fracture patients at the end of acute care?—a prospective observational study

Abstract: Acute care of hip fracture patients should be focused on functional recovery and treatment of depression. When the preferred surgical strategy is unclear, joint replacement should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 44 publications
6
23
2
1
Order By: Relevance
“…They noted that high levels of functioning prior to fracture (including good motor function, independence in living status and undertaking activities of daily living) were associated with better QoL post fracture. In contrast to our study, Buecking et al [33] determined the factors correlated with EQ-5D score at discharge from an acute hospital among hip fracture patients. They identified significant bi-variate correlations between age, pre-fracture co-morbidity and functional status, pre-fracture residential status, MMSE on admission, type of surgery (prosthesis vs internal fixation) and presence of delirium and EQ-5D scores at discharge.…”
Section: Discussioncontrasting
confidence: 94%
“…They noted that high levels of functioning prior to fracture (including good motor function, independence in living status and undertaking activities of daily living) were associated with better QoL post fracture. In contrast to our study, Buecking et al [33] determined the factors correlated with EQ-5D score at discharge from an acute hospital among hip fracture patients. They identified significant bi-variate correlations between age, pre-fracture co-morbidity and functional status, pre-fracture residential status, MMSE on admission, type of surgery (prosthesis vs internal fixation) and presence of delirium and EQ-5D scores at discharge.…”
Section: Discussioncontrasting
confidence: 94%
“…In contrast to Bellelli et al (2012) who found that joint replacement was associated with a higher risk of unsuccessful recovery of pre-fracture walking ability, our results suggested that a prosthesis implantation was associated with better mobilization at the end of acute care, compared to patients who received internal fixation (Tables 5 and 6). Consistently, in our patient sample, internal fixation was also associated with poorer quality of life at the end of acute care (Buecking et al, 2013). From our results, it is not possible to conclude that all hip fractures should be treated with joint replacement.…”
Section: Discussionsupporting
confidence: 63%
“…At our acute care trauma department of the university hospital Marburg, we performed a prospective, observational, cohort study that included 402 patients older than 60 years with proximal femoral fractures (ICD-10 S72.0-72.2 [ICD-10]) (Buecking et al, 2013). The exclusion criteria for this study were polytrauma (ISS !…”
Section: Methodsmentioning
confidence: 99%
“…We saw little use of the EQ-5D-instrument at one year, without any pre-fracture data to compare with. Obtaining prefracture EQ-5D result by recall technique has been done in several studies [21][22][23] but may be obscured by cognitive limitations in the elderly, often aggravated by pain, medication and surgery during the period when the interview would be performed. Comparing EQ-5D to age-matched tariffs may also be misleading, as hip fracture patients usually are frailer than their peers.…”
Section: Pain (Vas) Satisfaction (Vas) Eq-5d Indexmentioning
confidence: 99%